2022
DOI: 10.3390/molecules27227759
|View full text |Cite
|
Sign up to set email alerts
|

Formulation of the Polysaccharide FucoPol into Novel Emulsified Creams with Improved Physicochemical Properties

Abstract: Driven by the customers’ growing awareness of environmental issues, the production of topical formulations based on sustainable ingredients is receiving widespread attention from researchers and the industry. Although numerous sustainable ingredients (natural, organic, or green chemistry-derived compounds) have been investigated, there is a lack of comparative studies between conventional ingredients and sustainable alternatives. In this study, olive oil (30 wt.%) and α-tocopherol (2.5 wt.%) containing oil-in-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(19 citation statements)
references
References 83 publications
3
16
0
Order By: Relevance
“…Both formulations presented high E24 values (98-99% for Prunus amygdalus dulcis oil emulsions and 89-96% for Olea europaea fruit oil emulsions), for all tested L-ascorbic acid concentrations (Table 2). These values are identical to those reported for FucoPol-based emulsion (98%) with the same contents in Olea europaea fruit oil (30%) and α-tocopherol (2.5%) (formulation C) [24]. based emulsion (98%) with the same contents in Olea europaea fruit oil (30%) and α-tocopherol (2.5%) (formulation C) [24].…”
Section: Defining L-ascorbic Acid Concentration In the Emulsions' Con...supporting
confidence: 85%
See 2 more Smart Citations
“…Both formulations presented high E24 values (98-99% for Prunus amygdalus dulcis oil emulsions and 89-96% for Olea europaea fruit oil emulsions), for all tested L-ascorbic acid concentrations (Table 2). These values are identical to those reported for FucoPol-based emulsion (98%) with the same contents in Olea europaea fruit oil (30%) and α-tocopherol (2.5%) (formulation C) [24]. based emulsion (98%) with the same contents in Olea europaea fruit oil (30%) and α-tocopherol (2.5%) (formulation C) [24].…”
Section: Defining L-ascorbic Acid Concentration In the Emulsions' Con...supporting
confidence: 85%
“…It was also demonstrated that FucoPol, as well as FucoPol-based emulsified creams, promoted migration of HFFF2 and HaCaT cells [20,21]. FucoPol's capacity as an emulsifier [22][23][24] was also reported. Baptista et al [22] showed FucoPol's high performance as an emulsifier for olive oil/α-tocopherol emulsions, with its presence improving the physicochemical and structural characteristics of the emulsions.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Droplet-based microfluidics presents a versatile platform for a broad range of applications such as cosmetic cream and lotion formulation, 166 molecular detection, supra magnetic nanoparticle synthesis, diagnostic tests and assays, and targeted drug delivery with biodegradable nanoparticles, among others. 167 A remarkable stride in the field of autonomous devices that feature self-propulsion has been achieved with the recent development of a micro surfboard propelled by droplets, inspired by the water strider.…”
Section: Classificationmentioning
confidence: 99%
“…It offers several advantages, including high viscosity, excellent compatibility, good stability, and excellent tissue compatibility [21][22][23]. Numerous functional polysaccharides are available, capable of serving as film formers, gelling agents, thickeners, conditioners, and emulsifiers, such as hyaluronic acid, which is applied as a moisturizing and bioactive ingredient [24,25].…”
Section: Introductionmentioning
confidence: 99%